The Yahukimo Conflict within the Ideal Narratives of Pancasila and Multiculturalism - Masykur Masykur (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2021)
The ideology of Pancasila is agreed upon to reconcile ethnic, religious, racial and intergroup diversity. However, tribal fanatism clashes in understanding inevitably lead to social conflicts, such as the tribal conflict in Yahukimo Papua. Based on this background, there are research questions, first, why do tribal social conflicts still exist in the Pancasila ideology state? How is Pancasila ideology able to be main foundation of the resolution of tribal social conflict? Methodologically, this paper is the result of literature study research. To explain the research questions, Bhikhu Parekh's theory of multiculturalism is used. In addition, the literature study method is used for data collection and the sociological approach for data analysis. The results of this study can be concluded that first, social conflicts with tribal nuances in the Pancasila ideological state will continue to have the potential to emerge when national identity is not maintained with a commitment to nationalism. Second, for this reason, the ideology of Pancasila in must continue to be carried out structurally and culturally for the resolution of tribal social conflicts. In the future, it is hoped that the Pancasila will ideally be embedded to strengthen national identity and unity.